Trp-Containing Antibacterial Peptides Impair Quorum Sensing and Biofilm Development in Multidrug-Resistant Pseudomonas aeruginosa and Exhibit Synergistic Effects With Antibiotics - Shang, Dejing; Han, Xue; Du, Wanying; Kou, Zhiru; Jiang, Fengquan (Frontiers in Microbiology, 2021)
P. aeruginosa uses quorum sensing (QS) to control virulence, biofilm formation and antibiotic ef-flux pump expression. The development of effective small molecules targeting the QS system and biofilm formation represents an attractive novel strategy. We investigated the effects of a series of Trp-containing peptides on the QS-regulated virulence and biofilm development of multidrug-resistant P. aeruginosa, as well as their synergistic antibacterial activity with three classes of tradi-tional chemical antibiotics. The results showed that Trp-containing peptides at low concentrations reduced the production of the QS-regulated virulence factors by downregulating the gene expres-sion of both the las and rhl systems in MRPA0108. Biofilm formation was inhibited in a concentra-tion-dependent manner, which was associated with extracellular polysaccharide production inhibi-tion by downregulating pelA, algD, and pslA transcription. These changes correlated with altera-tions in the extracellular production of the pseudomonal virulence factors and swarming motility. In addition, the combination of Trp-containing peptides at low concentration with the antibiotics ceftazidime and piperacillin provided synergistic effects. Notably, L11W and L12W showed the highest synergy with ceftazidime and piperacillin. A mechanistic study demonstrated that the Trp-containing peptides, especially L12W, signiﬁcantly decreased β-lactamase activity and the expres-sion of efflux pumps OprM, MexX and MexA genes, resulting in a reduction in antibiotic efflux from MRPA0108 cells and thus increasing the antibacterial activity of these antibiotics against the MRPA0108 strain.